Chawki Silkworm Performance on Selected Mulberry Hybrids in Different Seasons - , Sushmitha C; Chikkalingaiah, Yashaswini B. R, Sapna J.S (Archives of Current Research International, 2025)
Nutritional indices help to find out the quantity of leaf required to produce the silk. It also helps to study conversion rate of ingested food by the silkworm, so that we can analyze the distribution rate of mulberry intake in silkworm for various factors like growth rate, silk production and faecal matter. The first, second and third instar silkworm Bombyx mori were reared on eight elite mulberry hybrids & two check varieties.The larvae fed on ME-65 × V1 recorded higher consumption index (0.89),(1.03),(1.09),growth rate (2.25), (2.44), (2.52) and larval weight (0.094g/20 larvae),(0.393g/20 larvae),(2.377g/20 larvae) at first, second and third instar during winter, summer and rainy season respectively. Whereas minimum consumption index (0.46), (0.54), (0.58) growth rate (1.70), (1.91), (1.98) and larval weight (0.062/20 larvae), (0.357g/20 larvae), (2.339g/20 larvae) was recorded when silkworms were reared on ME-67 × V1 at first, second and third instar during winter, summer and rainy season respectively. The variation of growth rate among mulberry accessions might be due to difference in biochemical constituents present in the mulberry varieties.